2012
DOI: 10.1002/ps.3317
|View full text |Cite
|
Sign up to set email alerts
|

Response of imidazolinone‐tolerant and ‐susceptible volunteer oilseed rape (Brassica napus L.) to ALS inhibitors and alternative herbicides

Abstract: Herbicide strategies have to be adjusted for volunteer control in subsequent crops if imidazolinone-tolerant oilseed rape varieties are to be grown. However, agronomic tools (harvest date, harvest technique, tillage) should be used conscientiously in the first place to keep volunteer oilseed rape densities at the lowest possible level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…No tilling reduces weed biomass significantly and therefore reduces biodiversity. Apparition of HT volunteers with time is strongly dependent on the crop management system used (Krato et al 2012) and has not been considered here (see Section 4.1).…”
Section: Gm Crops Marginally Improve Environmental Sustainabilitymentioning
confidence: 99%
“…No tilling reduces weed biomass significantly and therefore reduces biodiversity. Apparition of HT volunteers with time is strongly dependent on the crop management system used (Krato et al 2012) and has not been considered here (see Section 4.1).…”
Section: Gm Crops Marginally Improve Environmental Sustainabilitymentioning
confidence: 99%
“…Imidazolinone tolerance was implemented in the OSR genome by conventional breeding methods due to mutagenesis [10]. Non-CL OSR varieties would perish after an imidazolinone treatment [11].…”
Section: Introductionmentioning
confidence: 99%
“…CL herbicides have high efficacy against cruciferous weeds, which are hard to control with common agents in OSR. Common OSR volunteers can be controlled in CL OSR crops, and thus, the CL-System can contribute to a reduction of an OSR soil seed bank as long as its prevention strategies are working after the establishment of CL OSR in a crop rotation [7,10,11]. Greenhouse trials have shown that when = CL varieties are grown, similar yields are achieved as when non-CL varieties are used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazolinone-resistant canola cultivars were developed from two mutants, called PM1 and PM2, which were obtained by induced mutagenesis of microspores (Krato et al 2012). The PM1 mutant, with a serine to asparagine substitution at codon 653, is resistant to imidazolinones only, and PM2, with a codon 574 modification, from tryptophan to leucine, is resistant to imidazolinones and sulfonylureas (Krato et al 2012).…”
Section: Introductionmentioning
confidence: 99%